Climate Anxiety and Human Survival in Contemporary English Literature - Kaur, Rajdeep (Journal of Ecohumanism, 2025)
The growing climate crisis has intensified global concerns regarding environmental degradation, psychological distress, and human survival, which are increasingly reflected in contemporary English literature. This research paper examines the representation of climate anxiety and human survival in selected contemporary climate fiction (Cli-Fi) texts through an eco-critical and thematic analytical framework. The study utilizes a contemporary climate fiction literary corpus dataset comprising selected novels, including The Water Knife, Gun Island, Migrations, and Oryx and Crake, collected from digital literary repositories such as Project Gutenberg and Internet Archive. The research explores how modern literary narratives portray ecological collapse, environmental trauma, extinction fears, climate migration, and emotional instability caused by climate change. Eco-criticism, trauma theory, and qualitative textual analysis are employed to identify recurring themes of ecological fear, survival strategies, and psychological distress within literary discourse. The findings reveal that contemporary English literature increasingly presents climate change as both an environmental and existential crisis threatening social stability, identity, and the future of humanity. The study further emphasizes the role of literature in fostering environmental awareness and emotional engagement with ecological realities. By integrating literary studies with environmental humanities, this paper contributes to interdisciplinary discussions on climate discourse, eco-anxiety, and human resilience in an era of ecological uncertainty.